MOTIVATIONAL BODYBUILDING VIDEOS AS A COMPONENT OF DISCOURSE INFLUENCING PERCEPTIONS OF MASCULINITIES - MADEJ, KACPER (Society Register, 2021)
The cult of a slim and beautiful body is no longer characteristic only for women. The male body is becoming more frequently subjected to the pressure of modelling. The use of different regimes increasingly intends to fulfil the requirements of attractiveness and physical perfection, also among men and boys. The discourse of disciplining the male body and its expectations also influence socially acceptable ways of performing gender. Employing a qualitative analysis of bodybuilding motivational films’ content, the author points out the key elements of the body project image in such materials. The possibility of identifying bodybuilders with experts in body modification, resulting from the specificity of the discipline, allows one to believe that the regimes and training tools presented by them can influence the perception of the body modelling process by men. The author presents four elements used to develop an image of the male body project – (1) conditions necessary for the project, (2) tools used in the project, (3) ways of controlling and evaluating the project, (4) side effects of the project. Based on them demonstrates how motivational bodybuilding films can affect changing ways of performing masculinity.